EFFECT OF BOARD GENDER DIVERSITY ON THE PERFORMANCE OF COMMERCIAL BANKS IN KENYA - Wachudi, Ekadah John; Mboya, Josphat (European Scientific Journal, ESJ, 2012)
The purpose of this paper was to analyze the effect of board gender diversityon performance of commercial banks in Kenya for the period 1998-2009. Stepwise regression was used to analyze the effect of board diversity on performance. It was found that boards of commercial banks in Kenya are male-dominated. On average, out of a typical board size of 8 members, only 1 is a female director. Finally, this study finds that board diversity has no effect on performance of banks in Kenya.